Loneliness Mediates the Relationship Between Early Life Stress and Perceived Stress but not Hypothalamic–Pituitary–Adrenal Axis Functioning - Crespo-Sanmiguel, Isabel; Zapater-Fajarí, Mariola; Pulopulos, Matias M.; Hidalgo, Vanesa; Salvador, Alicia (Frontiers in Psychology, 2021)
Many authors have proposed that early life stress (ELS) provokes a dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis and contributes negatively to the management of stress in adulthood. However, these associations have not always been observed, making it necessary to include new factors that could explain the different results found. In this regard, people with ELS experiences report less social support during adulthood, suggesting that loneliness could be a mediating factor. Thus, our aims were to investigate whether ELS was related to both perceived stress and diurnal HPA axis activity, and whether loneliness mediates these relationships, in a community sample (N=187, 18–55years old). Fourteen cortisol samples were collected on two non-consecutive days to obtain the overall diurnal cortisol, diurnal cortisol slope, and bedtime levels. Additionally, ELS was assessed with the Risky Families Questionnaire (RFQ) and the Recalled Childhood and Adolescence Perceived Stress (ReCAPS) measure. Results revealed that ELS was associated with perceived stress, but not HPA axis functioning, and loneliness mediated the relationship between ELS and perceived stress, but not between ELS and HPA axis functioning. Similar results were found for both ELS questionnaires, suggesting that the ReCAPS is an adequate tool. These results highlight the importance of loneliness in understanding the long-term effects of ELS, and they indicate different effects of ELS on subjective and physiological stress indicators.